Prevention of tuberculosis in those HIV-infected in Siberian Federal District - E. S. Dovgopolyuk; L. V. Puzyreva; L. I. Levakhina; A. V. Mordyk; A. T. Tyumentsev; A. D. Safonov (Туберкулез и болезни лёгких)
In order to evaluate the efficiency and scope of tuberculosis prevention activities conducted among those HIV-infected in Siberian Federal District the statistic data for 5 years have been derived from annual reports and main statistic forms and analyzed. The coverage with preventive screening for tuberculosis among the HIV-infected is high in the district and makes 99.9% (by X-ray). 96.1% of HIV patients have been examined for secondary disorders including tuberculosis. The frequency of tuberculosis preventive chemotherapy in those with immune suppression due to HIV goes up every year. However the main pool of those falling ill with tuberculosis are the patients at the late stages of HIV-infection. This unfavorable situation is due to the lack of motivation and treatment and examination compliance in those living HIV thus it results in the increase of tuberculosis epidemics in HIV patients.